Exploring the Landscape of Researching the Teaching Practicum in the ELT Context (2021)
This paper describes a review of the research developed on the English Language Teaching Practicum (ELTP) as part of a doctoral study on the senses of the ELTP through the experiences and interrelations of the English language teaching practicum community (ELTPC): preservice teachers (PTs), school and university mentors, (SMs-UMs [1]) in the Colombian context. In the first part, the paper situates the ELTP in Initial Language Teacher Education (ILET) and elaborates on the contributions Colombian English Language scholars have made in regard to the ELTP. This review portrays instructional processes, reflective approaches, beliefs, expectations and dichotomies, identity construction, and research as a central axis in ELTP core tendencies. The majority of the studies continue to invisibilize the three-voiced experiences of those subjects who live the ELTP. In the second part, the paper discusses pedagogical colonialism in English Language Teaching (ELT) extended to the ELTP as a static-limited conceptualization that normalizes ELTP. From a decolonial standpoint, I would affirm that understanding the senses of the ELTP through the experiences and interrelations of pre-service teachers, school, and university mentors might contribute to questioning the hegemonic views rooted in epistemic perspectives of the Global North that have dominated the ELT field and therefore the ELTP. Furthermore, we can comprehend the holistic formation processes that pre-service teachers go through with their SMs and UMs to envision different ways of being, doing, and thinking about the plurals and particularities of the ELTP. [1] These terms are used in this paper to address cooperating teachers and university advisors, which have been traditionally named in the literature.